2022
DOI: 10.3389/fneur.2022.886609
|View full text |Cite
|
Sign up to set email alerts
|

Dysautonomia in COVID-19 Patients: A Narrative Review on Clinical Course, Diagnostic and Therapeutic Strategies

Abstract: IntroductionOn March 11, 2020, the World Health Organization sounded the COVID-19 pandemic alarm. While efforts in the first few months focused on reducing the mortality of infected patients, there is increasing data on the effects of long-term infection (Post-COVID-19 condition). Among the different symptoms described after acute infection, those derived from autonomic dysfunction are especially frequent and limiting.ObjectiveTo conduct a narrative review synthesizing current evidence of the signs and symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 91 publications
0
49
0
Order By: Relevance
“…Some of the symptoms displayed in Figure 1 are likely to be due to dysautonomia [ 14 ]. Autonomic dysfunction appears to be a rather frequent feature of the post-COVID condition and can cause, for example, orthostatic intolerance syndromes, neurogenic orthostatic hypotension, labile blood pressure, postural orthostatic tachycardia syndrome [ 15 ], and other more non-specific sequelae, such as gastrointestinal symptoms (e.g., abdominal pain, vomiting, constipation, or loose stools), flushing, sweating abnormalities, or temperature intolerance [ 14 ].…”
Section: Symptoms and Sequelae Of Post-covid Syndromementioning
confidence: 99%
“…Some of the symptoms displayed in Figure 1 are likely to be due to dysautonomia [ 14 ]. Autonomic dysfunction appears to be a rather frequent feature of the post-COVID condition and can cause, for example, orthostatic intolerance syndromes, neurogenic orthostatic hypotension, labile blood pressure, postural orthostatic tachycardia syndrome [ 15 ], and other more non-specific sequelae, such as gastrointestinal symptoms (e.g., abdominal pain, vomiting, constipation, or loose stools), flushing, sweating abnormalities, or temperature intolerance [ 14 ].…”
Section: Symptoms and Sequelae Of Post-covid Syndromementioning
confidence: 99%
“…Autonomic dysfunction including POTS and neurogenic orthostatic hypotension have been frequently observed in post-COVID-19 patients as well as in the setting of other viral infections. [110][111][112][113] A systemic review reported that approximately 2.5% of patients with COVID-19 infection develop autonomic dysfunction. 110 Jamal et al evaluated 24 patients with symptoms of poor exercise intolerance, tachycardia with activity or positional changes, and palpitations 5.8 AE 3.5 months following acute infection.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…[110][111][112][113] A systemic review reported that approximately 2.5% of patients with COVID-19 infection develop autonomic dysfunction. 110 Jamal et al evaluated 24 patients with symptoms of poor exercise intolerance, tachycardia with activity or positional changes, and palpitations 5.8 AE 3.5 months following acute infection. 114 Head-up tilt table testing was performed with 23 of 24 patients demonstrating orthostatic intolerance.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…Standard treatment of POTS is well described and established. 144 With a diagnosis of POTS, we first recommend fluid replacement (2-3 liter of water per day, avoiding caffeine and alcohol). Additionally, we try saline infusion, 1-2 L/day.…”
Section: Examinations For Specific Symptomsmentioning
confidence: 99%